A Study on Extent of Counseling by Hospital Pharmacists - Thapa, Raj Kumar; Joshi, Isha; Thapa, Prakriti; Bajracharya, Nashreen; Neupane, Joshika; Thapa, Sushma; Dhakal, Sita; Acharya, Trishna (Journal of Advanced Academic Research, 2018)
Pharmacists can improve adherence to drug therapy in order to help patients participate in their own health care decision. The study aimed to observe the problems faced during dispensing and counseling. A cross-sectional study was carried out in two different hospitals of Nepal. ASHP (American Society of Health-System Pharmacy) 1997 and USP (The United States Pharmacopoeia) 1997 guidelines were used to ensure the completeness of the contents of the counseling. The extent of counseling fulfilled by the pharmacists was observed and recorded. Collected data was compiled, managed and analysed using SPSS and MS Excel. Counseling was observed in total 400 cases (200 from each hospital). It was found that complete information from the guidelines was not provided in both the hospitals. Hospital pharmacists of urban region had provided maximum 5 categories of drug information while it was 6 in sub-urban region out of 14 categories given by USP and 16 categories given by ASHP guidelines. Besides this, none of them had received any counseling regarding precaution, side effects/adverse effects, interactions, contraindication, sensitivity and storage of the medications. Further, it was found that poly-pharmacy, language, lack of qualified personnel in pharmacy, inadequate time, lack of space in the pharmacy were some of the barriers to counseling found in the study. The minimum requirements of the guidelines were met in both the hospitals. However, the safety aspects of drug information were not provided to the patients. Prioritizing the safe and effective use of medicines should be the first consideration of the pharmacists.